Membangun Kepercayaan dan Loyalitas Melalui Edukasi dan Literasi Keuangan untuk Meningkatkan Retensi dan Advocacy Nasabah Bank Syariah - Marshelynda, Alfia Rahmadhanti; Nisa, Fauzatul Laily (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
This study investigates the relationship between financial education, customer trust and loyalty in Islamic banking. This research explores how these factors influence customer retention and advocacy. This research uses a descriptive qualitative research design with a focus on describing the phenomenon under study. The data collection used secondary data. Secondary data includes published materials such as books, archival records, and reports of previously conducted research. The findings show that financial education has a positive impact on customer trust and loyalty. Customers who have a deeper understanding of Islamic banking products and services show higher levels of trust and loyalty towards the bank. This, in turn, will increase customer retention and advocacy, where satisfied customers will recommend the bank to others. This research emphasizes the importance of Islamic banks implementing strategies to improve customer financial literacy. This can result in a stronger customer base with increased retention and advocacy.